KINERJA KOORDINASI SIMPANG BERSINYAL JALAN RAJAWALI – JALAN GARUDA (SIMPANG I) JALAN RAJAWALI – JALAN TINGANG (SIMPANG II) KOTA PALANGKA RAYA - Muhammad Ikhsan Sidiq (Lambung Mangkurat University Press, 2018)
The Rajawali Road intersection is a Collector Road section where along the road there are many Shops, Schools, Healt Facility, Hotels and Residential Residents. On the Rajawali Road there are 2 (two) four-arm crossing points where the distance between the two crossing points is 540 meters. The two adjacent intersections are Jalan Rajawali and Jalan Garuda (intersection I) and Jalan Rajawali and Jalan Tingang (intersection II). The study aims to determine the performance of Intersections I and Intersections II in existing conditions and provide a choice of solutions so that the level of service of the two intersected signals becomes better. Primary data collection is done by direct observation in the field, data components taken through observations in the form of intersection traffic volume, intersection geometrics, and cycle times. Whereas in calculating to find out the performance at Intersection I and Intersection II, it was conducted using MKJI approach. The solution is implemented to improve service at both intersections by changing the phases of the two intersections and then coordinating the signals at both intersections manually. The results of the performance at the existing conditions of peak hour hours showed the highest value of delay at intersection I was 78.79 sec / pcu with service level E, while at intersection II the delay value was 47.71 seconds with Service Level Index E value for peak hour afternoon. After the signal coordination scenario is done by equating the two phases, namely 3 phases and the change in cycle time at Intersection I for 50 seconds and Intersection II for 50 seconds, the average delay value at intersection I is 27.38 sec / pcu with service value D for afternoon peak hours and intersection II of 30.30 sec / junior high with service value D. The application of signal coordination between Intersection I and Intersection II has maximized the performance of intersections and service levels at Intersection I and Intersection II.